Genetic Basis of Synchrony in Pod Maturity in Mungbean (Vigna radiata (L.) Wilczek) - Khattak, G. S. S.; Haq, M. A.; Ashraf, M.; Tahir, G. R. (Agriculture and Natural Resources, 2001)
The inheritance of early flowering, early pod maturity and synchrony in pod maturity was studied in six diverse mungbean genotypes through the diallel crossing design. The genotype NM 92 was the best general combiner for early flowering and early pod maturity, whereas accession ML-5 was the best general combiner for more synchrony in pod maturity. The best specific combination for early flowering and early pod maturity was NM 92 x NM 89 and for highest synchrony in pod maturity was NM 92 x ML-5. The days to first pod and 90% pod maturity, and degree of indetermination from first flower to 90% pod maturity (DDd1) were controlled by both additive and dominance gene effects with predominant effect of additive component. Only additive and dominance gene effects controlled the days to first flower and degree of indetermination from first pod maturity to 90% pod maturity (DDd2), respectively. The high narrow and broad sense heritability for days to first flower, days to first pod maturity and 90% pod maturity revealed more proportion of their genetic variation due to additive gene effects. The selection for synchrony in pod maturity is suggested to be made in advanced generation due to the low narrow sense heritability for degree of indetermination from first flower to 90% pod maturity.